Politik dan Cinta Tanah Air dalam Perspektif Islam - Zalkhairi, Zalkhairi; Aulia, Quratul; Syukri Azhari, Devi (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Politics and love of one's country in an Islamic perspective are two interrelated concepts in building a just and prosperous society. Islam views politics as a tool to realize the benefit of the people with the principles of justice, deliberation and trustworthy leadership. Love for one's homeland in Islam does not only mean love for one's place of birth, but also the obligation to protect, build and defend a country based on sharia values. This concept is based on the teachings of the Koran and hadith which emphasize the importance of unity, social justice and mutual prosperity. Thus, Islamic politics aims to uphold leadership that is oriented towards the welfare of the people, while love of the homeland is a manifestation of the people's responsibility in maintaining the integrity and progress of the nation.